Feasibility, acceptability and effectiveness of asthma education delivered by community health workers in improving asthma control in children and adolescents: a protocol for a cluster-randomized trial in Uganda - Rebecca Nantanda; Levicatus Mugenyi; Andrew Sentoogo Ssemata; Sarah Namusoko; Phiona Ekyaruhanga; Mary Kuteesa; Fred Matovu; Jonathan Grigg (BMC Pediatrics)
Abstract Background Asthma control is a major challenge particularly in low and middle-income countries where access to care is still poor. Asthma education is a cornerstone in self-management and achieving asthma symptom control. However, there is limited human resources to offer asthma education in low-resources settings. This study will investigate the feasibility, acceptability and effectiveness of community health worker (CHW)-led asthma education in improving asthma control among children and adolescents in Uganda. Methods The study will employ a cluster-randomized trial (CRT) study design. It will be conducted in 8 primary care health facilities (HFs) in Jinja region, Eastern Uganda. The HFs will be randomly assigned to the control and intervention arms in the ratio 1:1. The sample size will be 300 children (150 per arm), and asthma control, emergency care visits and hospitalizations will be assessed at baseline, month 1,3 and 6. Asthma education will be provided by CHWs known as Village Health Teams (VHTs) at each visit. Data on direct and indirect costs of asthma education will be collected prospectively. Focus Group Discussions (FGDs) will be conducted among VHTs and caregivers of participating children at the intervention sites to assess the feasibility and acceptability of the intervention. To estimate the mean difference in asthma control scores between the intervention and control arms, adjusted for baseline scores and facility-level clustering, we shall use a random-effects linear regression model and intention-to-treat analysis. The primary endpoint will be asthma control scores. Cost-effectiveness will be assessed by computing the Incremental Cost-Effectiveness Ratio. Thematic content analysis will be used to analyze data from the FGDs. Discussion It is anticipated that the study will provide evidence about the role of community health workers in supporting the care of patients with asthma and achieving symptom control, through providing health education. The data on feasibility, acceptability and cost-effectiveness will be critical in informing scale up plans. Trial registration number ISRCTN16018011. Date: 25/05/2024.